2021
DOI: 10.18502/jfrh.v14i4.5204
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Screening for Thyroid Dysfunction in Preconception and Pregnancy: An Evidence-Based Review

Abstract: Objective: To evaluate the recommendations on the most adequate screening method (universal or selective) for thyroid dysfunction. Although thyroid dysfunction is a common disorder in fertile women and untreated cases may have negative maternal, fetal and neonatal outcomes, its screening in preconception and early pregnancy is controversial. Materials and methods: An evidence-based review was conducted to identify publications since 2017 of American Thyroid Association (ATA) guidelines, according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given the association between thyroid disease and unfavorable pregnancy outcomes, the question of whether or not universal thyroid screening during pregnancy should be implemented has sparked debate. The low prevalence of thyroid disorders reported in the literature and the varying levels of thyroid-stimulating hormone across the globe are central to this discussion [9].…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between thyroid disease and unfavorable pregnancy outcomes, the question of whether or not universal thyroid screening during pregnancy should be implemented has sparked debate. The low prevalence of thyroid disorders reported in the literature and the varying levels of thyroid-stimulating hormone across the globe are central to this discussion [9].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing relatively recent literature on this topic (2015 onwards), those in favour of universal screening for thyroid dysfunction in pregnancy point to the relatively high prevalence of thyroid disorders, the existence of low-cost tests (TSH, T4) and treatment (LT4), the potential of screening to avoid the potential devastating consequences of undiagnosed thyroid disease at this time, its cost-effectiveness, and a better prospect of finding most or all cases, compared with a targeted screening approach focussed on individuals with risk factors for thyroid disease ( 58 , 59 , 60 , 61 ). In one study, targeted screening focussed on women with at least one risk factor for hypothyroidism found that this approach was more effective for detecting overt hypothyroidism than SCH (except for obese Caucasian women, where both were detected) ( 62 ).…”
Section: Should We Screen For Thyroid Dysfunction During Pregnancy?mentioning
confidence: 99%
“…Total thyroxine and the FT4 index can also be measured in its place. Definitive screening is performed only in high-risk pregnant women (Figure 3) using serum TSH measurements [16], [17]. One study found that selective screening for high-risk women will be lost 30% of those with subclinical hypothyroidism.…”
Section: Thyroid Dysfunction Screening In Pregnancyimentioning
confidence: 99%